Five traditional Nigerian Polyherbal remedies protect against high fructose fed, Streptozotocin-induced type 2 diabetes in male Wistar rats - O. E. Kale; O. B. Akinpelu; A. A. Bakare; F. O. Yusuf; R. Gomba; D. C. Araka; T. O. Ogundare; A. C. Okolie; O. Adebawo; O. Odutola (BMC, 2018)
Abstract Background This present study sought to assess the modulatory effects of five Nigerian traditional polyherbal in high fructose-fed, streptozotocin-induced (HF-STZ) Type 2 diabetes (T2D) in rats. T2D was achieved via fructose feeding (20% W/V ) ad libitum for 2 weeks and streptozotocin (STZ, 40 mg/kg) (15th Day) intraperitoneally. Methods Seventy-two hours after STZ injection, fourty-eight diabetic rats were divided into eight of 6 rats/group: Diabetic normal untreated, glibenclamide (GBLI, 0.07 mL/kg) or yoyo (YB, 0.43), ruzu (RB, 0.08), fajik (FJB, 0.20), oroki (OB, 0.16), and fidson (FB, 0.43)/ mL/kg bitters respectively. Controls normal and diabetic untreated groups received intragastric carboxylmethylcellulose (CMC, 1 mL/kg) for eleven days. Results T2D was characterized in rats by an increased (p < 0.001-0.05) blood glucose levels (BGL), total cholesterol, triglycerides, low-density lipoprotein and alanine aminotransferase compared with control CMC group. Similarly, hepatic and pancreatic malondialdehyde (MDA) were increased by 180 and 97% respectively. Polyherbal treatments demonstrated efficacies on BGL as follow: YB (55.6%, 160.7 mg/dL); RB (59.7%, 145.2 mg/dL); FJB (59.8%, 243.4 mg/dL); OB (60.8%, 194.5 mg/dL) and FB (61.3%, 203.3 mg/dL) respectively by day 11 (versus GBLI, 65.1%) compared with control untreated diabetic rats. Also, elevated TC, LDL cholesterol, ALT were lowered (p < 0.05) by YB, FJB, and FB respectively in rats. YB, FJB, and OB lowered MDA levels in treated rats. Further, YB, RB, FJB and FB restored changes in liver, and pancreas histopathology. Predominant non-polar bioactive include oleic, hexadecanoic, octadecanoic among others following gas chromatography-mass spectrophotometry analyses. Conclusion Overall, these present results demonstrate anti-hyperglycemic potentials, although with cautions, of some polyherbal in T2D rats, which may, in part, be antioxidants mediated.